Sistematización de resultados del Programa de Mejoramiento Cualitativo de la Educación en Institutos Técnicos Profesionales de Costa Rica - José Ramírez-Alfaro (Universidad Nacional, Costa Rica, 2007)
This article shows results obtained in the Program of Qualitative Improvement of Education in Costa Rican Technical Institutes of five different regions: North Region, Limon, South Region, Central Pacific (Aguirre) and Santa Cruz. This experience was designed at the Technical Institutes as a pilot project, developing situational diagnoses and interventional action plans for the improvement, specially, of infrastructure and didactic equipment. Subsequently, a planning stage of verification, curriculum development and tactic planning was carried out. This is a methodological proposal for the qualitative improvement of education in these Technical Professional Institutes.